Effect of the Different Growth Shapes on the Electrochemical Behavior of Ti Thin Films for Medical Applications - Bertapelle, Matteo; Borges, Joel; Mirza-Rosca, Julia Claudia; Vaz, Filipe (MDPI AG, 2025)
The response of titanium (Ti) thin films is closely related to their microstructure, which is extremely sensitive to the selected deposition parameters and geometrical configurations. The present study investigates the impact of geometrical factors on the growth of Ti thin films, focusing on how variations in growth geometry influence film microstructure, surface morphology, and corrosion resistance. Three Ti thin films were prepared using Glancing Angle Deposition (GLAD) in a custom-built DC reactive magnetron sputtering system. For the first sample, the target was positioned perpendicular to the substrate surface (α = 0◦); for the second and third samples, the substrate holder was positioned at an angle of 85◦ regarding the target direction (α = 85◦), incorporating a 180◦ azimuthal rotation for the last (to obtain a zigzag-like deposition). The thickness and morphological features of the thin films were investigated by SEM, while the surface morphology, specifically roughness, and crystallinity of the thin films were assessed by AFM and XRD, respectively. Continuous and alternating current techniques were used for electrochemical characterization of behavior in simulated body fluid. The obtained results show a clear tendency to an improvement in anticorrosion performances varying the nanoarchitecture of the films in comparison to the conventional-grown sample, with the inclined sample presenting a slight enhancement in corrosion resistance and the zigzag-grown sample having the best corrosion resistance properties of the three.
Keywords: thin film; titanium; medical applications; SEM; EIS; growth geometry